The stress and ballistic properties of granular materials - Proud, W; Chapman, D; Eakins, D (AIP Publishing, 2017)
Granular materials are widespread in nature and in manufacturing. Their particulate nature gives a compressive strength of a similar order of magnitude as many continuous solids, a vanishingly small tensile strength and variable shear strength, highly dependent on the loading conditions. Previous studies have shown the effect of composition, morphology and particle size, however, compared to metals and polymers, granular materials are not so well understood. This paper will present some recent results for granular materials, placing these within the wider context. Two areas will be dealt with (i) the effect of the skeletal strength of the material and (ii) the displacements associated with ballistic impact. One clear observation is the similarity of behavior of quartz-sands in compression across a range of particle size. However, the precise pathway of compression is strongly dependent on the initial conditions e.g. density and connectivity within the granular bed, as emphasized by some data for quasi-static compression of sand. To fully embrace the range of behaviours seen requires the development of a suitable parameter to describe the material, the paper concludes with a discussion of one of those approaches.